Analisis Hambatan dan Tantangan dalam Membina Anak yang Berkonflik dengan Hukum pada Usia Peralihan di Lembaga Pemasyarakatan Pemuda Kelas IIA Tangerang - Mohammad Supriadi (Perantara Law Review, 2024)
The construction of transitional-age children in the Youth Correctional Facility in the future, in accordance with Article 86 of Law No. 11 of 2012 concerning the Juvenile Justice System (SPPA), faces implementation obstacles and main challenges for transitional-age children in the Youth Correctional Facility. The purpose of this research is to find an ideal model for the correctional facility for transitional-age children. The research method used in this study is normative-empirical legal research. The findings of this research show that there are obstacles such as the absence of specific legal regulations governing the guidance of transitional-age children, limited human resources impacting the ineffective implementation of the parole program, and the still high societal stigma not only towards inmates but also towards products resulting from correctional activities. In the future, it is necessary to establish a specific correctional model for children in conflict with the law in accordance with the Juvenile Justice System Law. This can be achieved by ensuring the precision of the institution through the revitalization of the Youth Correctional Facility to restore its original purpose. Additionally, a reactualization of guidance guidelines is needed by updating the implementation of criminal laws, such as creating technical regulations in the form of ministerial regulations. Furthermore, in terms of the precision of the correctional model, it can be achieved by using the Un-Absolute Individual Treatment approach and supported by programs oriented towards certified work skills.